The Influence of Digital Platform Capabilities on Innovation Performance Mediated by Value Co-Creation in SMEs - Bimawan, Fitnantyo; Widowati, Lis; Kurniawati, Andi (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to analyze the impact of digital platform capability on innovation performance in SMEs, with value co-creation serving as a mediating variable. Data were collected through a questionnaire distributed to 100 SME respondents in Semarang who utilize digital platforms in their business operations. Data analysis was conducted using SPSS 26, employing multiple regression methods and the Sobel mediation test. The results indicate that digital platform capability has a significant positive effect on the innovation performance of SMEs. Furthermore, value co-creation was found to mediate this relationship, thereby enhancing the impact of digital platform capability on innovation performance. These findings underscore the importance of integrating digital technology with collaboration through value co-creation to improve competitiveness and innovation performance among SMEs in a dynamic market. Keywords: Digital platform capability, innovation performance, value co-creation, SMEs, SPSS.